Conceptualising early childhood care and development in fragile states: Understanding children and childhood in Myanmar. Issue 4 (December 2015) - Ang, Lynn; Wong, Lily
Accelerating political and economic reforms in Myanmar are shaping the country considerably. In a fast-changing national landscape, Myanmar is a developing country in East Asia with a rapidly evolving early childhood sector. Although empirical research on early childhood in Myanmar is generally limited, it is likely that current reforms in the country and internationally will significantly influence the way children and childhood are defined and understood. This article will offer a critical discussion of constructions of childhood and the critical issues and debates pertaining to children's care and education. The article argues that competing national agendas, particularly in the context of fragile, developing nations with complex political and socio-economic conditions, present new challenges in shaping children's care and education. It contends that an inherent paradox remains in that while early childhood is increasingly recognised by governments as a 'public good', the early childhood sector, its governance and infrastructures face considerable challenges in a largely resource-limited environment, thus highlighting the stark disparity between aspirational policies and social reality. The article also presents an insight into an on-going longitudinal preschool teacher training project that began in 2003, developed collaboratively between the Myanmar government and a group of volunteer early childhood care and development specialists and organisations, as an illustration of how early care and education is being conceptualised in the country. In a wider global context, the discussion will also explore the ways in which international advocacy for children's rights, as reflected, for instance, through the Millennium Development Goals, is shifting the way children and childhood are perceived nationally and globally.